REPRESENTASI ISLAM: PAMERAN SENI RUPA ISLAM INDONESIA KONTEMPORER “BAYANG” - Zaenudin Ramli (Jurusan Seni Rupa ISBI Bandung, 2017)
In this paper the writer explores the capacity of Islamic identity and ummah to promote cross cultural understanding through displays of Islamic art and culture. The exhibition of contemporary Indonesian Islamic art entitled